2013
DOI: 10.7461/jcen.2013.15.3.221
|View full text |Cite
|
Sign up to set email alerts
|

Distal Subclavian Artery Occlusion Causing Multiple Cerebral Infarcts Consequence of Retrograde Flow of a Thrombus?

Abstract: Intracranial embolization usually arises from the heart, a vertebrobasilar artery, a carotid artery, or the aorta, but rarely from the distal subclavian artery upstream of an embolus. We report on a patient who experienced left shoulder and forearm pain with weak blood pressure and pulse followed by concurrent onset of left hemiplegia. This case is a rare example of multiple cerebral embolic infarctions, which developed as a complication of distal subclavian artery thrombosis possibly associated with protein S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The source of emboli was found to be an axillary artery aneurysm with intramural thrombus. A proposed mechanism is retrograde flow and embolization of the cerebral artery due to occlusion and lack of forward flow from the thrombosed peripheral artery [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The source of emboli was found to be an axillary artery aneurysm with intramural thrombus. A proposed mechanism is retrograde flow and embolization of the cerebral artery due to occlusion and lack of forward flow from the thrombosed peripheral artery [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies in patients with cryptogenic stroke have shown that a high proportion of these patients demonstrate retrograde embolization of aortic plaque that could reach all aortic branch vessels. 33,37,[39][40][41][42]…”
Section: Cryptogenic Strokementioning
confidence: 99%